Faith, Humanity, and Character in Higher Education: A Thematic Literature Review from Islamic Perspectives: Iman, Kemanusiaan, dan Karakter dalam Pendidikan Tinggi: Tinjauan Literatur Tematik dari Perspektif Islam - Faizah, Ima; Handayani, Puspita; Farihah, Anis (Journal of Islamic and Muhammadiyah Studies, 2026)
General Background Character education is increasingly emphasized in higher education to address contemporary moral and social challenges. Specific Background In Islamic higher education, character formation is closely linked to the integration of faith and humanity as core educational values. Knowledge Gap However, existing studies remain dispersed and lack a coherent synthesis explaining how these concepts are conceptualized and integrated. Aims This study aims to synthesize literature on faith and humanity within character education from Islamic educational perspectives. Results Based on a thematic literature review of 195 publications from 2020–2025, faith is conceptualized as taqwa reflected in noble character, while humanity represents compassion, empathy, justice, and ethical responsibility. Five themes emerge: spiritual–moral development, curriculum integration, institutional roles, pedagogical approaches, and implementation challenges. Novelty This review offers an integrated thematic framework linking faith and humanity in Islamic higher education character education. Implications The findings provide guidance for curriculum development, institutional policy, and pedagogical practices supporting holistic character education. Highlights: Faith as piety guides students' morals and ethical responsibilities. Humanity is reflected in empathy, justice, and social responsibility. Curriculum, institutional culture, and pedagogy shape character education. Keywords: Character Education, Islamic Higher Education, Faith, Humanity, Moral Development